2017
DOI: 10.4103/jcd.jcd_273_16
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of C-shaped canals in mandibular second and third molars in a central India population: A cone beam computed tomography analysis

Abstract: Introduction:To evaluate the prevalence of C-shaped root canals in mandibular molars using cone beam computed tomography (CBCT) in a subpopulation of Central India.Materials and Methods:CBCT scans of patients from diagnostic imaging center were selected in accordance with the criteria given by Fan et al. (2004) for C-shaped canals. A total of 238 CBCT scans fulfilled the inclusion criteria and thereby divided into two groups: Group 1: Images showing C-shaped canal configuration in mandibular second molars. Gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 19 publications
5
12
0
1
Order By: Relevance
“…Similar results but with a statistically significant difference were found in Koreans [31], Saudis [28] and Malaysians [32]. Regarding tooth location, Cshaped canals occurred almost even on both sides in this study with no significant difference similar to reports in Chinese [4], Iranians (35), Indians [29], and Koreans [31].…”
Section: Root Canal Typessupporting
confidence: 87%
See 3 more Smart Citations
“…Similar results but with a statistically significant difference were found in Koreans [31], Saudis [28] and Malaysians [32]. Regarding tooth location, Cshaped canals occurred almost even on both sides in this study with no significant difference similar to reports in Chinese [4], Iranians (35), Indians [29], and Koreans [31].…”
Section: Root Canal Typessupporting
confidence: 87%
“…C-shaped canals were found in females more than males with no significant difference same as reported in Chinese [4], Indians [29] and Iranians [8]. Similar results but with a statistically significant difference were found in Koreans [31], Saudis [28] and Malaysians [32].…”
Section: Root Canal Typessupporting
confidence: 70%
See 2 more Smart Citations
“…MSMs with C-shaped root showed mainly both lingual and buccal grooves, followed by lingual groove only, and then by buccal groove only, unlike findings in studies of Saudi Arabians ( 17 ), Koreans ( 8 ) and Chinese ( 4 , 20 ) which showed mainly only a lingual groove. Moreover, Wadhwani et al ( 29 ) reported MSMs mainly with a buccal groove only in Indians.…”
Section: Discussionmentioning
confidence: 99%